2006
DOI: 10.1108/02683940610684373
|View full text |Cite
|
Sign up to set email alerts
|

Trust‐in‐supervisor and helping coworkers: moderating effect of perceived politics

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 72 publications
(82 reference statements)
5
54
1
Order By: Relevance
“…Hence, this supports the idea that employees' behaviour can be affected by their working environment (Lee & Idris, 2017). This is particularly important considering the fact that Malaysia is a collectivistic country where the environment exerts considerable influences on individuals (Poon, 2006).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Hence, this supports the idea that employees' behaviour can be affected by their working environment (Lee & Idris, 2017). This is particularly important considering the fact that Malaysia is a collectivistic country where the environment exerts considerable influences on individuals (Poon, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…A study by Kiffin-Petersen and Cordery (2003) of 218 employees in 40 teams, for example, discovered that working in a high-trust environment led employees to higher levels of teamwork since they became more aware of opportunities for their skills to be utilised. This finding is also consistent with the suggestion that when there is a higher level of trust, more resources are available and exchanged, thus benefitting employees (Jain, Sandhu, & Goh, 2015;Poon, 2006). How management trust enhances personal development can be explained using a model of group development in which the way supervisors and subordinates trust each other may lead to proper processes and structures for task completion (see Kozlowski, Gully, Nason, & Smith, 1999).…”
Section: Management Trust and Job Resourcessupporting
confidence: 77%
“…Trust is an important factor in the relationship between superiors and subordinates (McCauley and Kuhnert, 1992 (Poon, 2006). Some studies indicated a direct effect of organizational trust on OCB (Podsakoff, et al, 1990;McAllister, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A three-item measure was developed to evaluate trust in co-workers. It was based on an instrument used by Forret and Love [107] and Poon [119]. Trust in co-workers was assessed by having participants indicate their level of agreement with the following statements: "Most of my co-workers can be relied upon to do their work", "Most of my co-workers are trustworthy", "I have confidence in my co-workers".…”
Section: Dependent Variablementioning
confidence: 99%